Management Analysis: Community Empowerment Based on Local Wisdom - Kusuma, Dedy Wijaya; Sari, Nurshadrina Kartika; Wahid, Abdul (Universitas Pendidikan Indonesia, 2024)
Tanoker Learning Village is unique in its community empowerment process based on local wisdom. Tanoker Village is complex, because it’s a structured organization that modifies traditional and modern culture and adopts innovations in the development of traditional and modern culture. This research aims to empower the community to play an active role in development activities. The reality of existing life, namely how local wisdom acts as social capital in empowering the community in Ledokombo Village. Research like this has not yet been carried out much in Indonesia. This research uses qualitative data with techniques interactive model of analysis to analyze local wisdom as strengthening social capital in community empowerment. The local wisdom values taught by the Tanoker Learning Village have succeeded in forming changes in individual consciousness, both in children, mothers, fathers and grandparents in Ledokombo Village. This change is visible in their thinking patterns and behavior. After following various guidance, their motivation changed to full awareness, where they wanted to contribute to making Ledokombo Village and its community better. In this case, it is proven that the Tanoker Ledokombo Learning Village acts as an agent of social change in rural areas of Ledokombo District through a local wisdom-based approach.